Pengaruh Perputaran Kas, Perputaran Piutang dan Perputaran Persediaan Terhadap Profitabilitas - Sufiana, Nina; Purnawati, Ni Ketut (E-Jurnal Manajemen; Vol 2 No 4 (2013), 2013)
The objective of this research is to determine the effect of cash turnover, receivable turnover, inventory turnover to profitability. Data used in this study were secondary data from food and beverages company financial statements in Indonesia Stock Exchange on the year of 2008 to 2010. The analysis method used is multiple linear regression, F test and T test. Result of these analysis showed that profitability was influenced simultaneously by cash turnover, receivable turnover and inventory turnover. Meanwhile on partial analysis showed only receivable turnover and inventory turnover has influence to profitability.   Keyword : profitability, cash turnover, receivable turnover, inventory turnover